Pengaruh Kemampuan Teknik Pemakai pada Kinerja Individual dengan Efektivitas Sistem Informasi Akuntansi Sebagai Variabel Pemoderasi - Bagus Acintiawan, I Kadek; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2019)
In order for the implementation of SIA to run effectively it requires a high level of user engineering capability which can certainly improve the individual performance of these users. This study uses an associative quantitative method. The data analysis technique used in this study is the analysis of Moderated Regression Analysis (MRA). The results of this study indicate that user technical abilities have a positive influence on individual performance in Savings and Loan Cooperatives in Badung Regency and the effectiveness of the Accounting Information System moderates the influence of user technical abilities on individual performance in Savings and Credit Cooperatives in Badung Regency. The implication in this study is that the higher the ability of the user technique, the higher the individual performance and the better the ability of the user technique will increase the effectiveness of the Accounting Information System so that individual performance will increase. Keywords : Accounting Information Systems; User Technical Capabilities;  Individual Performance.